IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION AND ETHICS LEARNING WITH THE INDEPENDENT CURRICULUM - Pratama, Jery; Liniar Salsa Junita; Lisda Mulina; Yuni Isnaini (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
This study aims to analyze the implementation of Islamic Religious Education and Ethics learning with the Independent Curriculum in class XI TKJ 3 SMK Negeri Indralaya Selatan. The research method used is qualitative descriptive with a case study approach. Data was collected through observation, interviews, and documentation. The results of the study show that the implementation of the Independent Curriculum in learning Islamic Religious Education and Ethics has had a positive impact on increasing student learning motivation. Students become more active and creative in following the learning process. Teachers are also more flexible in developing lesson plans and can tailor the material to the needs and interests of students. However, there are several obstacles, such as a lack of supporting facilities and limited time to evaluate the achievement of student competencies. Overall, the implementation of the Independent Curriculum in class XI TKJ 3 SMK Negeri Indralaya Selatan can improve the quality of Islamic Religious Education and Ethics learning, but further support is needed from the school and the government to overcome existing obstacles.